Analysis and simulation of 12 pulse rectifier circuits: article / Nurul Akmal Mohamad Nor - Mohamad Nor, Nurul Akmal (2010)
In this paper the autotransformer connection with reduced kVA capacities are presented for harmonic current reduction in power diode rectifier-type utility interface systems and also reducing in kVA rating compared to the convections! 12 pulse converter. Based on the concept of an autotransformer, a 12-pulse rectifier system is realized with resultant transformer kVA rating of 0A8Po (pu). In this arrangement the 5, 7, 17, 19, etc. harmonics are absent from the utility input line current Analytical design equations are presented to facilitate the design of the system components. Simulation results verify the proposed concept.